Peran Jam’iyah Shalawat Diba’ Kubra Terhadap Kerukunan Masyarakat Desa Sawiji Kecamatan Jogoroto Kabupaten Jombang - Shudur, Mishbahush; Samani, Samani (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2023)
This research aims to find out empirical and comprehensive information about the role of Jam'iyah Shalawat Diba' Kubra which is a forum for the community to build relationships in achieving harmony in Sawiji Village, Jogoroto District, Jombang Regency. This jam'iyah uses the traditional al-Banjari musical instrument, a traditional musical instrument that is played by hand and contains keys with the terms "lanang and wedok". This research uses a descriptive method with a qualitative approach. The data collection techniques used were interviews, observation and documentation. Meanwhile, to analyze the data, researchers carried out data reduction, data presentation and drawing conclusions. To validate the data using source triangulation techniques. The results of this research indicate that Jam'iyah Shalawat Diba' Kubra plays an optimal role in forming harmony in the Sawiji Village community. This role includes, among others, as a forum for community friendship to establish harmonious family relationships, as a forum for seeking knowledge through the advice of ulama relating to guidance in daily life as taught by the Prophet Muhammad, and as a forum for mutual cooperation that can increase harmony in society. Keywords: Diba' Kubra, Community Harmony